Targeting Zika virus with new brain- and placenta-crossing peptide–porphyrin conjugates - Todorovski, Toni (2022)
© 2022 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).